(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
A new actinopterygian genus and species, Chaohuperleidus primus gen. n. n. sp., is described from the Upper Member of the Nanlinghu Formation (Spathian, Olenekian, Early Triassic) at Majiashan (Majia Hill), Chaohu City, Anhui Province, Southeast China. The new taxon is assigned to the order Perleidiformes on the base of a combination of features: large wedge-like preoperculum with expanded infraorbital process and sensory canal running almost vertical along the posterior margin of the preoperculum itself, flank scalessomewhat higher than longer in the trunk region and presence of epaxial rays in the caudal fin.AmongPerleidiformes, the new taxonbelongsto thePerleididae, being very similar to Perleidus in the general body shape, pattern of the skull bones, the dentitionmade of peg-like marginal teeth,and number of epaxial rays. The new genus is characterized by the presence of a very large antero-dorsal process on the suboperculum, a high number (about 55) of transversal scale rows and dorsal and anal fin quite posterior. Chaohuperleidus gen. n., beingSpathianin age,represents the oldest record of the order Perleidiformes.